Analyzing the Relationship Between Energy Efficiency and Environmental and Financial Variables: A Way Towards Sustainable Development - Taskin, Dilvin; Dogan, Eyup; Madaleno, Mara (Pergamon-Elsevier Science Ltd, 2022)
The literature has mainly relied on an annual and short span of data to analyze the relationship between energy, environmental and financial indicators. This study analyzes the relationship between energy efficiency, energy research, pollution mitigation, and FinTech by applying two novel methods-the causality test in the frequency domain [11] and the causality test in the time domain (Shi et al., 2018; 2020) on the daily data from June 17, 2016 to November 16, 2021. Empirical results from the frequency domain test report that pollution mitigation temporarily causes energy efficiency only in the short run while energy efficiency Granger causes it in the short, medium, and long run. Furthermore, energy efficiency can predict FinTech in the short, medium, and long-run; on the other way, FinTech Granger causes energy efficiency in the long and medium run, suggesting a permanent causality relationship. Empirical results from the time-varying test show a bidirectional relationship between energy efficiency, and environmental and financial variables, especially with very high significant episodes around the recent pandemic collapse. Policymakers should promote the launch of financial technologies that will provide finance through green bonds for energy efficiency improvements as well as energy efficiency improvements for pollution mitigation. Further policy implications are discussed in the study.(c) 2022 Elsevier Ltd. All rights reserved.
Taskin, Dilvin/0000-0001-6139-8006; Madaleno, Mara/0000-0002-4905-2771;
Keywords: Energy Efficiency; Financial Technology; Pollution; Causality